Post-quench staging time behavior of cryogenically treated tool steel - Oconer, Irmin S. (2002.)
Conventional heat treatment of high alloy steel involves the process of heating the metal above the austenitizing temperature, soaking and quenching either in oil or air. During cooling, once the temperature has reached room temperature, it is then tempered in the furnace to impart toughness, improve dimensional stability, relieve residual stresses and develop secondary hardening and red-hardness property for hot-work and high-speed steels. Usually, tempering of tool steels is done twice in order to eliminate the presence of retained austenite. Presence of retained austenite is detrimental because of its ability to transform to martensite when heated. The effect of this transformation produces tremendous difficulty in the control of the dimension due to the crystallographic expansion of austenite to martensite (approximately 4% by volume). In the experiment, the % retained austenite as affected by two time variables; namely: time of post-quench stage soaking at room temperature and time of soaking in liquid nitrogen after post-quench stage soaking at room temperature were investigated. A total of 44 samples of NSI 02 (1.5 % C, 12 % Cr) tool steel were prepared, then, austenitized and quenched in oil at room temperature, the samples were soaked at different time intervals (0, 1, 2, 9, 20, 49, 81 , 121 , 144, 196, and 225 hours). At the end of each post-quench staging time, the samples were soaked in liquid nitrogen at different times (I, 8, 16, and 24 hours). X-ray diffractometer was used to measure the retained austenite that transformed to martensite. From the data plots, the variation of % retained austenite with either soaking time or post-quench staging time showed a linear relationship. The effect of either one of the independent variables (soaking time in liquid nitrogen, post-quench staging time at room temperature) appeared to be dependent on the level of the other independent variable, implying an interaction between the two. The dependence of this effect on the level of the other variable can be summarized as follows: Empirical relationship between effect of post-quench staging time on % retained austenite and soaking time: y = -0.0028 x + 0.0453 where y = effect of post-quench staging time at room temperature (in % retained austenite/hr) and x = soaking time in liquid nitrogen in hours; Empirical relationship between effect of soaking time in liquid nitrogen on % retained austenite and post-quench staging time at room temperature: y = -0.0037 x + 0.3284 where y = effect of soaking time in liquid nitrogen (in % retained austenite/hr) and x = postquench staging time at room temperature in hours. The results show that the effects of post-quench staging time at room temperature or soaking time are initially positive from 0 to 49 hours followed by an essentially linear decrease of the effect with time to a negative value for sufficiently longer times. A positive effect initially indicates that the treatment has a stabilization effect, a condition by which retained austenite no longer transforms to fresh martensite. The negative effect, however, indicates that at long post-quench soaking times, the stabilization effect on austenite is hindered and the retained austenite is transformed to martensite. This now favors a more dimensionally-stable tool steel.
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman.
Keywords: Tool-steel -- Quenching; Tool-steel -- Heat treatment